IMPLEMENTASI PENANAMAN NILAI-NILAI KARAKTER ISLAMI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA SMK: STUDI KUALITATIF DESKRIPTIF - Fadhlika Cahya Ningrum (PT. Sulthan Journal Publisher, 2026)
This study aims to describe the implementation of Islamic character values through Islamic Religious Education (IRE) learning among students at SMK PI Ambarrukmo 1 Sleman. This research employed a qualitative approach with a descriptive design. Data were collected through classroom observations of the learning process and documentation of activities in grades X, XI, and XII. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Islamic character values are integrated into learning activities through various instructional methods, such as lectures, discussions, question and answer sessions, projects, presentations, role play, and religious habituation. These habituations include greetings, prayers, congregational Dhuhr prayer, ablution practice, Qur’an reading, and memorization of prayer recitations. Islamic education teachers also serve as role models in shaping students’ character. However, some students were found to be less serious and not fully engaged in these practices. Therefore, the internalization of Islamic character values requires continuous guidance and collaboration within the school environment.